Chemical Quality of Chicken Bone Waste Gelatin Extracted using Chloride Acid - Ludfia Windyasmara; Ambar Pertiwiningrum; Novian Wely Asmoro; Afriyanti Afriyanti (Buletin Peternakan, 2018)
This study aims to isolate and extract the chicken bone gelatin through hydrolysis process and was analyzed chemically the extracted gelatin product. Research activities included several stages: (1) chicken bone waste preparation (2) ossein extraction (3) gelatin production (4) gelatin chemical analysis. The extraction time was 60 minutes with 5 treatment levels of HCl concentration ie K1 = 2%, K2 = 3%, K3 = 4%, K4 = 5% and K5 = 6%. Each treatment was repeated three times. Gelatin analysis consists of water content, ash content, protein content, pH value, viscosity, and gel strength. The highest water content was 15,76% at 2% HCl concentration, the highest ash content was 44,40% at 2% HCl concentration, and the highest protein content was 23,23% at 3% HCl concentration. The highest pH value was 4.14 produced by gelatin at 2% HCl concentration, viscosity was 5,13 cP and gel strength of 252,43, the best bloom was produced by gelatin at 6% concentration level. The conclusion of this research is the best quality of gelatin is obtained by using chicken bones and the use of chloride acid for 24 hours and 6% HCl concentration level.